PLANNING AND MONITORING THE EDUCATIONAL PROCESS IN PRIMARY GRADES: MODERN APPROACHES (World Bulletin of Social Sciences, 2025)
This article analyzes modern approaches to planning and monitoring the learning process in primary classes. The study demonstrates ways to optimize the learning process by using diagnostic tools, applying interactive methods, and focusing on individual development. Additionally, it examines pedagogical approaches aligned with the priorities of the New Uzbekistan Development Strategy in the field of education. The results contribute to improving students’ knowledge and skills, supporting personal development, and enhancing the quality of education.